Cloning and sequencing of a full-length sea bream (Sparus aurata) beta-actin cDNA - Santos, Cecilia (2014)
A full-length cDNA clone encoding beta-actin (b-actin) was isolated from a sea bream (Sparus aurata) liver cDNA library. Sequencing of this clone reveals an open reading frame encoding a 375 amino acid protein that shares a high degree of conservation to other known actins. The sea breamb-actin sequence showed 98% identity to carp and human b-actin and 95% and 94% identity to sea squirt and Dictyostelium cytoplasmic actins, respectively.